Innovating through tradition: kava-talanoa as a culturally aligned medico-behavioral therapeutic approach to amelioration of PTSD symptoms - Aporosa, S. Apo; Itoga, Dennis; Ioane, Julia; Prosser, Jan; Vaka, Sione; Grout, Emily; Atkins, Martin J.; Head, Mitchell A.; Baker, Jonathan D.; Blue, Tanecia; Sanday, David H.; Owen, Mahonri W.; et al. (Frontiers in Psychology, 2025)
Levels of post-traumatic stress disorder (PTSD), trauma-related distress, and subsyndromal PTSD, (here “PTS”) among combat soldiers and first responders are of international concern. In the broader population, a PTS global epidemic is attending trauma associated with the threatscape of the Anthropocene (increased extreme weather events, natural disasters, conflict, rising poverty, emerging infectious disease) as well as the legacy of the COVID-19 pandemic. PTS is also a health economic burden, with costs associated with treatment, long-term morbidity, and increased risk of mortality. In the Pacific region, rising PTS is associated with the existential threat of climate change and the economic and social legacy of colonization. There is an unmet therapeutic need for improved and culturally aligned PTS therapies in the Pacific and beyond. Medical standards of care for anxiety/PTS typically involve psychotropic interventions such as benzodiazepines (BDZ), tricyclic anti-depressants and anti-psychotic medications which have addictive potential, are only effective in the short term, are contraindicated for key populations such as the elderly and have significantly problematic track records in indigenous populations. Moreover, systemic racism both drives PTS in indigenous and other marginalized populations and limits the efficacy in such populations of conventional PTS therapies which are not culturally relevant or informed. Here, we describe the development of a novel, but traditionally grounded, approach to PTSD symptomatology in the context of Pacific populations. This approach has two elements: kava is a culturally significant Pacific drink used traditionally and in cultural practice, as a relaxant, to promote dialog in group settings, to aid in sleep and to manage anxiety. Its anxiolytic and sedative properties may link to the presence of kavalactones which are putative low potency γ-aminobutyric acid (GABA) ligands. Talanoa is a dialog practice common to most Pacific cultures. Our core hypothesis is that, combined, kava-talanoa will outperform current standards of care in PTSD symptom management as a culturally augmented cognitive-behavioral group therapy intervention. In this paper we review supporting literature, describe kava-talanoa pilot study findings and planned clinical trials, discuss important open questions, and present recommendations for broad-based transcultural applicability of this approach to global PTS burdens.